Exogenous DCPTA Treatment Increases Mung Bean Yield by Improving Carbon Metabolism Pathway and Up-Regulating Photosynthetic Capacity and Antioxidants - Gao, Yuling; Zhang, Xiaolin; Wang, Xin; Zhang, Qi; Tang, Huarong; Qiu, Tian; Zhang, HuiLai; Zhao, Bingxin; Wang, Hao; Liang, Xilong; Guo, Yongxia (Frontiers in Plant Science, 2022)
Abstract: Mung bean is characterized by a good edible and medicinal value, while its flowers and pods seriously have a low production. DCPTA (2-(3,4-dichlorophenoxy) triethylamine), being a tertiary amine, substantially regulates the growth and development of crops, maintaining its production. Yet it is still limited on the regulation of DCPTA on the growth and development, including yield and sugar metabolism of mung bean. Here, in this study, DCPTA was sprayed to the beginning of mung flowering through a two-season cultivation, assessing its effects on the yield, leaf area per plant, plant height, seed setting rate, photosynthesis, chlorophyll content, and endogenous protective enzymes. Experimental results illustrated that relative to control (CK), DCPTA application significantly (p<0.05) improved the yield of Bailv 11 mung bean, of which rose up to 6.9% in 2020 and 7.8% in 2021, respectively. This effect positively corresponded to a significant (p<0.05) increase in the number of pods and grains per plant and pod setting rate, but a non-significant difference in 1000-grain weight. DCPA application also increased the area and fresh weight of leaf, mung height, and its organ dry weight (i.e., leaf, branch, and stem). During plant growth over DCPTA application, the increased activities of SOD, POD, and CAT improved the net photosynthetic rate, stomatal conductance, and transpiration. In addition, transcriptome sequencing further demonstrated that DCPTA treatment significantly (p<0.05) up-regulated the sucrose synthase, invertase, and fructose kinase in all organs (i.e., leaves, pod skins, and grains) of plant. In particular, this effect was much greater in the sucrose synthesis (i.e., sucrose content) in leaves. Our study, therefore, concludes that DCPTA application promotes the yield of mung bean via likely enhancing its photosynthetic capacity and sucrose synthase, fructokinase, and beta-fructofuranosidase expression regulation.